2020
DOI: 10.3390/insects11090596
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Bioactivity of Ludwigia spp. in the Control of Plutella xylostella (Lepidoptera: Plutellidae)

Abstract: We tested the bioactivity of aqueous extracts of Ludwigia spp. (Myrtales: Onagraceae) on the biological cycle of Plutella xylostella. We assessed the duration of and viability during the larval, pupal and adult phases, as well as the influence of the extracts on the fecundity and hatching of P. xylostella eggs. Subsequently, we phytochemically screened the extracts. The extracts of L. tomentosa and L. longifolia reduced the pupal weight instead of prolonging the larval stage of P. xylostella. The L. tomentosa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 56 publications
4
17
0
4
Order By: Relevance
“…Tagetes species (Asteraceae) as well as M. azaderach (Meliaceae) and T. vogelii (Fabaceae) are other plants with an interesting potential to be tested, depending on cabbage production zones. Other unlisted extracts from plants ( Achillea millefolium (Asteraceae), Bidens pilosa (Asteraceae), Bougainvillea glabra (Nyctaginaceae), Chenopodium ambrosioides (Chenopodiaceae), Datura suaveolens (Solanaceae), Enterolobium contortisilliquum (Fabaceae), Stryphnodendron adstringens (Fabaceae) Mentha crispa (Lamiaceae), Plumbago capensis (Plumbaginaceae), Pothomorphe umbellate (Piperaceae), Sapindus saponaria (Sapindaceae), Solanum cernuum (Solanaceae), Symphytum officinale (Boraginaceae), Trichilia catigua (Meliaceae) and Ludwigia spp (Onagraceae)) [ 239 , 240 ] and management tactics (microbial control, biological control, cultural control, mating disruption, insecticide rotation strategies, and plant resistance) [ 241 ] have been explored on P. xylostella .…”
Section: Discussionmentioning
confidence: 99%
“…Tagetes species (Asteraceae) as well as M. azaderach (Meliaceae) and T. vogelii (Fabaceae) are other plants with an interesting potential to be tested, depending on cabbage production zones. Other unlisted extracts from plants ( Achillea millefolium (Asteraceae), Bidens pilosa (Asteraceae), Bougainvillea glabra (Nyctaginaceae), Chenopodium ambrosioides (Chenopodiaceae), Datura suaveolens (Solanaceae), Enterolobium contortisilliquum (Fabaceae), Stryphnodendron adstringens (Fabaceae) Mentha crispa (Lamiaceae), Plumbago capensis (Plumbaginaceae), Pothomorphe umbellate (Piperaceae), Sapindus saponaria (Sapindaceae), Solanum cernuum (Solanaceae), Symphytum officinale (Boraginaceae), Trichilia catigua (Meliaceae) and Ludwigia spp (Onagraceae)) [ 239 , 240 ] and management tactics (microbial control, biological control, cultural control, mating disruption, insecticide rotation strategies, and plant resistance) [ 241 ] have been explored on P. xylostella .…”
Section: Discussionmentioning
confidence: 99%
“…Such technique is for small producers and/or organic producers, due to its lower financial cost and the aggregation value to the final product, since besides applying good production practices, they align with ONU sustainable development goals (Agenda 2030) and the One Health principles (Cook et al 2004). Research about plant extracts reported insecticide properties such as mortality and feeding deterrence (Zhang et al 2001;Chandrashekharaiah et al 2015;Liu et al 2015;Matias da Silva et al 2017), larvicide effects (Hikal et al 2017;Ferreira et al 2020), reduction of fecundity (Ferreira et al 2020), repellence (Boiça Jr. 2013), morphological and physiological changes in P.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, su principal daño es el de afectar a la calidad del producto debido a la presencia de huevos y larvas que ocasiona su rechazado para la exportación (Da Silva Carvalho, 2008). Actualmente, en México, el control de la polilla de las crucíferas se basa principalmente en el empleo de plaguicidas químicos de amplio espectro (Tabone et al, 2010(Tabone et al, y 2012Ferreira et al, 2020). Desafortunadamente, la mayoría de esos plaguicidas son dañinos para el medio ambiente y se ha observado que producen múltiples efectos secundarios en ar-trópodos benéficos (depredadores, parasitoides y polinizadores) (Biondi et al, 2012;Lu et al, 2012;Ndakidemi et al, 2016).…”
Section: Introductionunclassified